Understanding Religious Moderation Of Hajj Pilgrims To Improve The Implementation Of Hajj In The Holy Land - Marfuddin, Ade; Arribathi, Abdul Hamid (AL-ADYAN, 2025)
Hajj embodies religious moderation in the implementation of worship for pilgrims in Saudi Arabia. This research aims to explore the attitudes, actions, and character of pilgrims while in the Holy Land. This study uses quantitative descriptive analysis and an interdisciplinary approach. The research sample comprises 58 flying groups (kloter) of pilgrims in 2025, totaling 775 respondents. Data were collected using a questionnaire survey through a Google form, and data processing was performed using the Statistical Package for the Social Sciences (SPSS). The findings of this study indicate that Indonesian pilgrims' level of understanding towards the concept of religious moderation is quite good. Both the level of education and the gender of pilgrims also affect their knowledge of religious moderation. Furthermore, the study highlights the need for religious collaboration through the guidance of Hajj manasik in the country. The suggestions and recommendations of this research are aimed at pilgrims, Hajj manasik supervisors, KBIH, Hajj manasik curriculum compilers, and the government to enhance the level of religious moderation among pilgrims. Keywords: Hajj; Religious Moderation; Holy Land.